2017
DOI: 10.1007/s12161-017-0830-5
|View full text |Cite
|
Sign up to set email alerts
|

Green and Efficient Extraction Method to Determine Polyphenols in Cocoa and Cocoa Products

Abstract: Cocoa and cocoa products have broad and wellproven health benefits, most of which are associated with the high antioxidant capacity of cocoa flavonoids. Most extraction methods for flavonoids in cocoa products use several steps including a defatting step and large amount of organic solvents. Moreover, they are labor-intensive and time-consuming. In this work, a pressurized hot water extraction (PHWE) method has been compared to conventional sonication extraction (CSE) method. The contribution of individual com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
(47 reference statements)
0
8
0
1
Order By: Relevance
“…The MSCE negative ion mode product of both of the compounds (chromatogram mass spectrum, low energy of mass spectrum, and high energy of mass spectrum) are shown in Figure 4 and Figure 5 . Previous studies report that epicatechin is found in fermented cocoa bean [ 44 ], cocoa pod husk [ 33 ], cocoa powder [ 45 ], and cocoa nibs [ 46 ]. Procyanidin trimer, procyanidin tetramer, procyanidin pentamer procyanidin B2, procyanidin C1, procyanidin B4, and procyanidin A2 are types of oligomers of flavonoids, and are found in the fermented and unfermented cocoa beans [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MSCE negative ion mode product of both of the compounds (chromatogram mass spectrum, low energy of mass spectrum, and high energy of mass spectrum) are shown in Figure 4 and Figure 5 . Previous studies report that epicatechin is found in fermented cocoa bean [ 44 ], cocoa pod husk [ 33 ], cocoa powder [ 45 ], and cocoa nibs [ 46 ]. Procyanidin trimer, procyanidin tetramer, procyanidin pentamer procyanidin B2, procyanidin C1, procyanidin B4, and procyanidin A2 are types of oligomers of flavonoids, and are found in the fermented and unfermented cocoa beans [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the process of extraction and the type of cocoa bean will give a different type of flavonoid and flavonoid yield. For comparison, procyanidin B and B2 were found in the different types of cocoa powder, nibs, and nibs powder, while procyaidin C is only found in the cocoa extract using sonication, but is not found in the pressurizes hot water extraction [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Total phenolic content was determined using Folin-Ciocalteu method described by Plaza et al (2017) with some modifications. Briefly, 10 μL of defatted sample extract was mixed with 3.0 mL of distilled water and 750 μL of 0.2N Folin-Ciocalteu reagent.…”
Section: Determination Of Polyphenol Contentsmentioning
confidence: 99%
“…Every year, 675 kt of cocoa bean shell (CBS) accrues as a waste stream in the food processing industry worldwide [20] and has high research interest [20,[23][24][25][26][27][28][29][30][31]. As a lignocellulosic biomass, CBS is a potential resource for β-glucans which can be utilized, for example, as bonding or binding agents.…”
Section: Introductionmentioning
confidence: 99%
“…As a lignocellulosic biomass, CBS is a potential resource for β-glucans which can be utilized, for example, as bonding or binding agents. Besides β-glucans, CBS contains a high amount of polyphenols such as catechin and epicatechin [23,28] and methylxanthines such as theobromine and caffeine. The development of process routes for the use of co-products is essential for the economic viability of these processes [32,33].…”
Section: Introductionmentioning
confidence: 99%